Experimental Study of the Influence of Even Harmonics on Flame Extinguishing by Low-Frequency Acoustic Waves with the Use of High-Power Extinguisher - Jacek Lukasz Wilk-Jakubowski (Applied Sciences, 2024)
The acoustic technique appears to be a novel and innovative way to extinguish flames, in which properly generated waves emitted by a high-power sound source are used for extinguishing purposes. The highest extinguishing efficiency is demonstrated by low-frequency waves. In practice, changing the parameters of the acoustic signal results in the possibility of universal and reusable use of the extinguisher, which is limited only by access to the power supply, unlike the currently known traditional methods of fighting fire (such as gases, foams, and extinguishing powders). The purpose of this paper is to analyze whether flame extinguishing by low-frequency acoustic waves is possible using signals containing higher harmonics with the use of large and very large powers delivered to the sound source, which is a scientific novelty. Analyzing the extinguishing capabilities of low-frequency acoustic waves allows one to fill the gap in the literature. This paper presents the results of research in the range of the influence of even sinusoidal harmonics on the extinguishing of flames originating from organic substances. For this purpose, in the experimental part, a high-power acoustic extinguisher and a point source of flames, i.e., a candle containing paraffin wax, were applied. The capabilities of the acoustic method in flame extinguishing have been experimentally demonstrated. The results address both the power that had to be delivered to the sound source of a high-power acoustic extinguisher to extinguish flames and the sound pressure level at which this phenomenon was observed. The added value is also to analyze how the order of even harmonics affects the process of acoustic extinguishment of flames (the order of harmonics for each fundamental frequency was varied from two to ten). Furthermore, the potential benefits and limitations of this method are explained, and future research directions are presented.